ANALISIS MOTIVASI BELAJAR SISWA SMP PADA MATERI BANGUN RUANG SISI DATAR BERBANTUAN GEOGEBRA - Zilan Jafirah Rohmatunnisa; Ika Wahyu Anita; Euis Eti Rohaeti; Ratna Sariningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research aims to analyze learning motivation on geogebra-assisted flat-sided space building materials. This research was conducted using qualitative descriptive methods. The subjects of this study were class VIII students of 6 people, consisting of 3 male students and 3 female students. The data collection technique uses a student learning motivation scale questionnaire on flat-sided space building materials supported by a geogebra application that contains 10 statements – 5 positive and negative statements respectively. The results of the analysis on this study showed that students were motivated by the use of the Geogebra application. The average student response is very strong. Using this Geogebra application proved to be very helpful for students on flat-sided room building materials.